The decolonial subject and the problem of non-Western authenticity. Issue 2 (3rd April 2019) - Vieira, Marco
ABSTRACT: It is argued in this paper that some decolonising strategies in the study of global politics are precluded by the problem of non-Western authenticity. I question the idea of an identifiable non-Western geo-cultural context that could significantly reconstitute what already is a post-Western subject. I claim that in most cases the asymmetrical encounter between the colonised and the coloniser has fundamentally and extensively redefined human subjectivity in a way that largely negates decolonial emancipatory projects. This is the result of the all-encompassing penetration of Western coloniality (in its political, economic and cultural representations) into the spaces of pre-colonial or uncolonised forms of subjectivity. I draw from Frantz Fanon's and Jacques Lacan's theories to argue that attempts to recover non-Western forms of self-identification are useful albeit illusory psychological mechanisms to stabilise hybrid postcolonial subjectivities rather than an actual restoration of non-colonial and purified forms of existing in the world. I suggest that an effective anticolonial politics of resistance will necessarily entail the understanding of post-Western subjectivity in terms of psychological 'hybridity' rather than decolonial 'authenticity'.